Non-specific low back pain: cross-sectional study of 11,423 children and youth and the association with the perception of heaviness in carrying of schoolbags - Agnieszka Kędra (PeerJ, 2021)
Background Carrying a schoolbag is a daily activity for most children and adolescents.The perception of a schoolbag’s weight depends upon the individual and is a relevant theme in schoolchildren. Describing the association between the perception of heaviness in carrying a schoolbag and NLBP can facilitate the planning of preventive programs, quite different from those based on specific weight limits for schoolbags in children and youth. Objective To determine the prevalence of non-specific low back pain (NLBP) and to analyse the association between the perception of heaviness in carrying of schoolbags and NLBP in Polish children and youth aged 10–19. Methods This study included 11,423 children and youth (6,252 girls and 5,171 boys) from Poland. An original questionnaire was used to assess NLBP prevalence. Results Among 11,423 of the respondents, 41.5% of the respondents admitted that they had experienced NLBP in the period of the last 12 months. The percentage of individuals reporting NLBP increased with age of participants, p < 0.001. Girls reported NLBP more often than boys (p < 0.001). Students with NLBP declared that their school backpack was heavy more often than students without LBP. Students who thought that their backpacks weighed too much manifested a 1.44 (95% Cl [1.33–1.55]) times higher probability to experience NLBP. Conclusion In the examined group of schoolchildren a frequent occurrence of NLBP (41.5%) was noted. Its occurrence was related to female sex and age. Students who thought that their backpacks weighed too much manifested higher probability to develop NLBP.